Seasonal Predictions of the Number of Tropical Cyclones in the Vietnam East Sea Using Statistical Models - Ba Duy, Dinh; Duc Thanh, Ngo; Quang Duc, Tran; Tan, Phan Van (VNU Journal of Science: Earth and Environmental Sciences, 2019)
Abstract: In this study, the equations for estimating the number of tropical cyclones (TCs) at a 6-month lead-time in the Vietnam East Sea (VES) have been developed and tested. Three multivariate linear regression models in which regression coefficients were determined by different methods, including 1) method of least squares (MLR), 2) minimum absolute deviation method (LAD), 3) minimax method (LMV). The artificial neural network model (ANN) and some combinations of the above regression models were also used. The VES was divided into the northern region above 15ºN (VES_N15) and the southern one below that latitude (VES_S15). The number of TCs was calculated from the data of the Japan Regional Specialized Meteorological Center (RMSC) for the period 1981-2017. Principal components of the 14 climate indicators were selected as predictors. Results for the training period showed that the ANN model performed best in all 12 times of forecasts, following by the ANN-MLR combination. The poorest result was obtained with the LMV model. Results for the independent dataset showed that the number of adequate forecasts based on the MSSS scores decreased sharply compared to the training period and the models generated generally similar errors. The MLR model tended to give out the best results. Better-forecast results were obtained in the VES_N15 region followed by the VES and then the VES_S15 regions. Keywords: Tropical cyclone, Seasonal prediction, Vietnam East Sea (VES). References : [1] W. Landsea Christopher, Gerald D. Bell, William M. Gray, Stanley B. Goldenberg, The extremely active 1995 Atlantic hurricane season: Environmental conditions and verification of seasonal forecasts, Mon. Wea. Rev. 126 (1998) 1174-1193. [2] W. Landsea Christopher, William M. Gray, Paul W. Mielke, Jr, Kenneth J. Berry, Seasonal Forecasting of Atlantic hurricane activity, Weather 49 (1994) 273-284. [3] M. Gray William, Christopher W. Landsea, Paul W. Mielke, Predicting Atlantic basin seasonal tropical cyclone activity by 1 June, Weather and Forecasting 9 (1994) 103-115. [4] Neville Nicholls, Chris Landsea, Jon Gill, Recent trends in Australian region tropical cyclone activity, Meteorol. Atmos. Phys. 65 (1998) 197-205. [5] Elsner, James B., Kam-biu Liu, Bethany Kocher, Spatial Variations in Major U.S., Hurricane Activity: Statistics and a Physical Mechanism, J. Climate. 13 (2000) 2293–2305. [6] J. C. L. Chan, J. E. Shi and C. M. Lam, Seasonal forecasting of tropical cyclone activity over the Western North Pacific and the South China Sea, Wea. Forecasting 13 (1998) 997-1004. [7] J. C. L. Chan, Tropical cyclone activity over the Western North Pacific associated with El Niño and La Niña events, J. Climate. 13 (2000) 2960-2972. [8] Pao-Shin Chu, Xin Zhao, Chang-Hoi Ho, Hyeong-Seog Kim, Mong-Ming Lu, Joo-Hong Kim, Bayesian forecasting of seasonal typhoon activity: A track-pattern oriented categorization approach, J.Climate. 23 (2010) 6654-6668 [9] M. Lu, P.-S. Chu, and Y.-C. Lin, Seasonal prediction of tropical cyclone activity near Taiwan using the Bayesian multivariate regression method, Wea. Forecasting 25 (2010) 1780–1795. [10] H. J Kwon, W.-J. Lee, S.-H.Won, E.-J. Cha, Statistical ensemble prediction of the tropical cyclone activity over the Western North Pacific.Geophys. Res. Lett. 34 (2007) L24805 1-5. doi:10.1029/2007GL032308 [11] J. C. L. Chan, Tropical cyclone activity in the Western North Pacific in relation to the stratospheric quasi-biennial oscillation, Mon. Wea. Rev. 123 (1995) 2567-2571. [12] J. C. L. Chan, Prediction of annual tropical cyclone activity over the Western North Pacific and the South China Sea, Int’l J. Climatol. 15 (1995) 1011-1019. [13] J. C. L. Chan, J. E. Shi and C. M. Lam, Seasonal forecasting of tropical cyclone activity over the Western North Pacific and the South China Sea, Wea.Forecasting 13 (1998) 997-1004. [14] J.C.L. Chan, J.E. Shi, K.S. Liu, Improvements in the seasonal forecasting of tropical cyclone activity over the Western North Pacific. Wea. Forecasting 16 (2001) 491-498. [15] P. J. Klotzbach, Recent developments in statistical prediction of seasonal Atlantic basin tropical cyclone activity, Journal compilation C (2007) Blackwell Munksgaard. https://doi.org/ 10.1111/j. 1600-0870.2007.00239.x, Tellus 59A (4) (2007) 511-518. [16] W. Zhang, Y. Zhang, D. Zheng, F. Wang, and L. Xu, Relationship between lightning activity and tropical cyclone intensity over the northwest Pacific, J. Geophys. Res. Atmos. 120 (2015) 4072 -4089. https://doi.org/10.1002/2014JD022334. [17] Phan Van Tan, On the tropical cyclone activity in the Northwest Pacific basin and South China sea in relationship with ENSO, Journal of Science, Vietnam National University, Hanoi (1) 18 (2002) 51-58. (In English) [18] Nguyễn Văn Tuyên, Xu hướng hoạt động của xoáy thuận nhiệt đới trên Tây Bắc Thái Bình Dương và biển Đông theo các cách phân loại khác nhau, Tạp chí KTTV 559 (2007) 4-10. [19] Đinh Bá Duy, Ngô Đức Thành, Phan Văn Tân, Mối quan hệ giữa ENSO và số lượng, cấp độ Xoáy thuận Nhiệt đới trên khu vực Tây Bắc - Thái Bình Dương, Biển Đông giai đoạn 1951-2015, VNU Journal of Science: Earth and Environmental Sciences 32 (3S) (2016) 43-55. [20] Đinh Bá Duy, Ngô Đức Thành, Nguyễn Thị Tuyết, Phạm Thanh Hà, Phan Văn Tân, Đặc điểm hoạt động của Xoáy thuận Nhiệt đới trên khu vực Tây Bắc Thái Bình Dương, Biển Đông và vùng trực tiếp chịu ảnh hưởng trên lãnh thổ Việt Nam giai đoạn 1978-2015, VNU Journal of Science: Earth and Environmental Sciences (2) 32 (2016) 1-11. [21] Đinh Văn Ưu, Đánh giá quy luật biến động dài hạn và xu thế biến đổi số lượng bão và áp thấp nhiệt đới trên khu vực Tây Thái Bình Dương, Biển Đông và ven biển Việt Nam, Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ (3S) 25 (2009) 542-550. [22] Nguyễn Văn Hiệp và nnk, Đặc điểm hoạt động của bão ở Tây Bắc Thái Bình Dương và Biển Đông qua số liệu Ibtracs, Tuyển tập báo cáo tại Hội thảo khoa học năm 2016 của Viện Khoa học KTTV & BĐKH, (2006) 9-14. [23] Vũ Thanh Hằng, Ngô Thị Thanh Hương,, Phan Văn Tân, Đặc điểm hoạt động của bão ở vùng biển gần bờ Việt Nam giai đoạn 1945-2007, Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ (3S) 26 (2010) 344‐353. [24] Nguyễn Văn Tuyên, Khả năng dự báo hoạt động mùa bão biển Đông Việt Nam: Phân tích các yếu tố dự báo và nhân tố dự báo có thể (Phần I), Tạp chí KTTV, 568 (2008) 1-8. [25] Nguyễn Văn Tuyên, 2008: Khả năng dự báo hoạt động mùa bão biển Đông Việt Nam: Phân tích các yếu tố dự báo và nhân tố dự báo có thể (Phần II). Tạp chí KTTV, 571 (2008) 1-11. [26] Phan Văn Tân, 2009-2010, Nghiên cứu tác động của biến đổi khí hậu toàn cầu đến các yếu tố và hiện tượng khí hậu cực đoan ở Việt Nam, khả năng dự báo và giải pháp chiến lược ứng phó. Đề tài cấp Nhà nước, mã số KC08.29/06-10. [27] https://www.jma.go.jp/jma/jma-eng/jma-center/ rsmc-hp-pub-eg/besttrack.html. [28] https://www.esrl.noaa.gov/ psd/data/climateindices/ list/ [29] T. Ngo-Duc, J. Matsumoto, H. Kamimera, H.H. Bui, Monthly adjustment of Global Satellite Mapping of Precipitation (GSMaP) data over the VuGia–ThuBon River Basin in Central Vietnam using an artificial neural network. Hydrological Research Letters 7 (4) (2013) 85-90. https://doi.org/ 10.3178/hrl.7.85. [30] J. C. L. Chan, J. E. Shi and C. M. Lam, Seasonal forecasting of tropical cyclone activity over the Western North Pacific and the South China Sea, Wea. Forecasting 13 (1998) 997-1004. [31] E. S. Blake, W. M. Gray, Prediction of August Atlantic Basin Hurricane Activity. Wea. Forecasting 19 (2004) 1044-1060. [32] P. J. Klotzbachi, W. M. Gray, Extended range forecast of Atlantic seasonal Hurricane activity and U. S. landfall strike probability for 2008, (2007) http://hurricane.atmos. colostate.edu/Forecasts.